PHENOMENOLOGY PRESERVE THE HEALTH OF FUTURE TEACHERS TO PROFESSIONAL ACTIVITIES UNDER HIGHER EDUCATION - Pobyrchenko, Neonyla A. (Educological discourse, 2015)
In the article the scientific ideas of phenomenology implementation in practice of the health of future teachers to the profession in terms of higher education; phenomenology health preservation formally presented as independent activities of self education students - learning; S students learning activities recommended to investigate how tumor preserve health in developing students’ readiness synerhuvaty phenomenological features of health; series actually operating functions of psychological and pedagogical knowledge and skills aimed at health care as a means of forming scientific integrity psycho-pedagogical professional activity of the future teacher.